Agresivitas Pajak : Manajemen Laba, Komisaris Independen, dan Intensitas Persediaan - Anis Febriana; Adhitya Putri Pratiwi (Jurnal Penelitian Ekonomi Akuntansi, 2023)
The purpose of this study is to determine the effect of Profit Management, Independent Commissioners, and Inventory Intensity on Tax Aggressiveness. This study uses a sample of Consumer Non-Cyclicals Sector Companies on the Indonesia Stock Exchange in 2017-2021. The data used in this study are financial statements and annual reports. The sampling of this study used the purposive sampling method and based on existing criteria, 31 company data were obtained and analyzed using panel data regression techniques with fixed effect models to test the hypothesis. Data is processed with the help of Eviews 9 software. The results obtained show that simultaneously profit management, independent commissioners, and inventory intensity have an effect on tax aggressiveness. The results obtained show partially that profit management affects tax aggressiveness, independent commissioners have no effect on tax aggressiveness, and inventory intensity affects tax aggressiveness. This research is limited to the Consumer Non Cyclical Sector with the majority of independent commissioners amounting to 30% of the total commissioners so it is unable to prove its effect on tax aggressiveness. It is hoped that future researchers can continue this research by making changes to the sectors used and focusing on sectors with an independent board of commissioners ownership percentage of more than 30%.